TRANSFORMASI MEDIA SOSIAL DALAM DIGITALISASI AGAMA: Media Dakwah dan Wisata Religi - Ahmad Rizal, Derry; Maula, Rif'atul; Idamatussilmi, Nilna (Kopertais Wilayah III Yogyakarta, 2024)
The development of technology and social media has shifted the style of interaction between communities. This is evidenced by the way of communicating and searching for the information needed. This research will examine how the transformation of social media in the digitalization of religion? And how is the use of social media for religious activities of religious tourism, and da'wah media? Research with a variety of social media that is popular among the public with a focus on several accounts on Youtube, Instagram and Tiktok as a limitation of social media in the context of religious activities. In this analysis, we will refer to Manuel Castells' view of network society which shows how information and communication technology has changed the way individuals and communities interact, including in the context of da'wah and religious tourism. The result obtained is that the transformation that occurs, religious activities in digital form become an alternative to promote and current information needs. Another thing, through a variety of platforms, it becomes a fad for the current generation, by browsing the application and the intended platform.